\(x^4+2x^3+5x^2+4x-12=0\)
\(\Leftrightarrow\)\(x^4-x^3+3x^3-3x^2+8x^2-8x+12x-12=0\)
\(\Leftrightarrow\)\(x^3\left(x-1\right)+3x^2\left(x-1\right)+8x\left(x-1\right)+12\left(x-1\right)=0\)
\(\Leftrightarrow\)\(\left(x^3+3x^2+8x+12\right)\left(x-1\right)=0\)
\(\Leftrightarrow\)\(\orbr{\begin{cases}x-1=0\\x^3+3x^2+8x+12=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=1\\x^3+2x^2+x^2+2x+6x+12=0\end{cases}}}\)
\(\Leftrightarrow\)\(\orbr{\begin{cases}x=1\\\left(x+2\right)\left(x^2+x+6\right)=0\end{cases}}\)
\(\Leftrightarrow\hept{\begin{cases}x=1\\x=-2\\x^2+x+6=0\left(1\right)\end{cases}}\)
Giải pt ( 1 ) \(x^2+\frac{1}{2}x.2+\frac{1}{4}+\frac{23}{4}=0\)
\(\Leftrightarrow\)\(\left(x+\frac{1}{2}\right)^2+\frac{23}{4}=0\)suy ra pt ( 1 ) vô nghiệm
Vậy pt có 2 nghiệm là x = 1 ; x = -2
x4 + 2x3 + 5x2 + 4x - 10 = 0
x4 - x3 + 3x3 - 3x2 + 8x2 - 8x + 12x - 12 = 0
<=> x3(x - 1) + 3x2(x - 1) + 8x(x - 1) + 12(x - 1) = 0
\(\Leftrightarrow\orbr{\begin{cases}x-1=0\\x^3+3x^2+8x+12=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=1\\x^3+2x^2+x^2+2x+6x+10=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=1\\\left(x+2\right)+\left(x^2+x+6\right)=0\end{cases}}\)
\(\Leftrightarrow\hept{\begin{cases}x=1\\x=-2\\x^2+x+6=0\left(1\right)\end{cases}}\)
Giải (1) \(x^2+\frac{1}{2}x.2+\frac{1}{4}+\frac{23}{4}=0\)
\(\Leftrightarrow\left(x+\frac{1}{2}\right)^2+\frac{23}{4}>0\Rightarrow\text{PT}\left(1\right)\)Vô nghiệm
=> PT có 2 nghiệm: \(\hept{\begin{cases}x=1\\x=-2\end{cases}}\)